STRATEGI PENENTUAN LOKASI GLOBAL PERUSAHAAN (STUDI KASUS DI STARBUCKS JAKARTA) - Rosalina, Sylvia Sari (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this study is to analyze consumer perceptions towards the location strategy used by Starbucks Corporation in Jakarta, Indonesia. The sample consists of 90 Starbucks consumers in Jakarta. This study uses descriptive analysis based on the results of the questionnaires distribution on respondents. The results show that the location strategy used by Starbucks Corporation in Jakarta has significant effect in increasing the number of customers and the product value which resulting in the increased company profit. Keywords: Location Strategy, Starbucks, Indonesia